A worldwide collaboration to harmonize guidelines for the long‐term follow‐up of childhood and young adult cancer survivors: A report from the international late effects of Childhood Cancer Guideline Harmonization Group1. Issue 4 (31st December 2012) - Kremer, Leontien C.M.; Mulder, Renée L.; Oeffinger, Kevin C.; Bhatia, Smita; Landier, Wendy; Levitt, Gill; Constine, Louis S.; Wallace, W. Hamish; Caron, Huib N.; Armenian, Saro H.; Skinner, Roderick; Hudson, Melissa M.
Abstract Childhood and young adult cancer survivors should receive optimum care to reduce the consequences of late effects and improve quality of life. We can facilitate achieving this goal by international collaboration in guideline development. In 2010, the International Late Effects of Childhood Cancer Guideline Harmonization Group was initiated. The aim of the harmonization endeavor is to establish a common vision and integrated strategy for the surveillance of late effects in childhood and young adult cancer survivors. With the implementation of our evidence‐based methods, we provide a framework for the harmonization of guidelines for the long‐term follow‐up of childhood and young adult cancer survivors. Pediatr Blood Cancer 2013; 60: 543–549. © 2012 Wiley Periodicals, Inc.